OP0120 Cause of death in a prospective study of ra patients: do rheumatology drugs play a part?. (1st June 2001) - Stafford, S; Mayes, CA; Young, A; Williams, P
Abstract : Background: Few prospective studies in RA have reported on the occurrence of comorbid conditions and mortality, and what proportion could be either disease or treatment related. The Early Rheumatoid Arthritis Study (ERAS) has prospective outcome data on patients followed for as long as 13 years. Objectives: To classify the cause of death and investigate any possible relationship with second line (disease modifying), steriodal or non steroidal anti-inflammatory drugs (NSAIDs). Methods: Consecutive patients with RA of less than two years duration have been recruited into an inception cohort from 9 rheumatology units. 1500 patients have been recruited into the study, prior to the use of second line drugs within 2 years of onset of symptoms of RA. Standard clinical and laboratory data were recorded yearly. Details of medication have been collected prospectively. Nearly all patients received non steriodal anti-inflammatory drugs (NSAIDs) at some stage, 84% received second line (disease modifying) drugs and 4% steroids alone. 166 deaths have been recorded from clinical notes, death certificates and the NHS Central Register (NHSCR). Cause of death has been catergorised according to both aetiology and main organ involvement. Results: Major causes of death in 166 patients (males n = 71 and females n = 95) were as follows: cardiovascular disease (n = 56, 33.7%), cerebrovascular (n = 14, 8.4%), malignancy (n = 45, 27.1%) and respiratory (n = 32, 19.3%). Pulmonary infections were recorded in 22 of the latter, Pulmonary Fibrosis in 6 (2 on methotrexate, but present prior to start of therapy), and others (n = 4). 19 miscellaneous conditions included gastrointestinal haemorrhage (n = 4, NSAID related in 3) and septicaemia (n = 5, 2 on steroids and 1 with neutropenia probably methotrexate induced). Conclusion: No direct link could be established between cause of death and rheumatoid disease or drug therapy in most patients, except those with Pulmonary Fibrosis (4%), and in 6 patients where drug therapy could have been a contributory factor to cause of death.